Foaming and surface properties of gliadin nanoparticles: Influence of pH and heating temperature. (April 2018) - Peng, Dengfeng; Jin, Weiping; Tang, Cuie; Lu, Ying; Wang, Wenqiang; Li, Jing; Li, Bin
Abstract: Foaming behavior strongly depends on the structural characteristics of protein colloidal particles. These characteristics may be modified by means of changes in pH value or temperature. In this paper, the foaming and surface properties of gliadin nanoparticles (GNPs) treated by different pH values (3.0–5.8) and heat temperatures (25–70 °C) were investigated. First, decreasing of the pH value (from 5.8 to 3.0) is a process that pHs stay away from isoelectric point (pI∼6.5) of gliadin. Accordingly, zeta potential of GNPs, as indicator of surface charge, rose from +16.3 to +22.0 mV with decreasing the pH from 5.8 to 3.0. But the particle size of GNPs decreased slightly. Meanwhile, the foamability (FA) and foam stability (FS) of GNPs significantly decreased, evidenced by the slow initial adsorption rate and low viscoelastic modulus at the air/water interface. Heating induced a growth of GNPs particle size, however, the zeta potential remained unchanged. The FA and FS of GNPs after heat treated at different temperature values (25–70 °C) kept at the high values and the bubble size maintained the same level. FA and FS of heated GNPs were good enough to board the application of GNPs in the food processing. To compare the effect of pH and temperature on GNPs surface behavior, our results found that the zeta potential played leading role on the adsorption rate of GNPs onto the air/water interface instead of particle size and morphology. Besides, for the foaming properties of GNPs, sensitivity of pH and non-sensitivity of heating give an instructor for further applications. Graphical abstract: Image Highlights: The foamability, foam stability, and adsorption rate of GNPs decreased as the pH decreasing from 5.8 to 3.0. Heat treatment did not show a significant influence on the foamability, foam stability, and adsorption rate of GNPs. The adsorption rate of GNPs onto the air/water interface was related to the zeta potential rather than particle size.